2021
DOI: 10.4049/jimmunol.2000551
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Epigenetic Programming and Enhanced Heme Metabolism Drive Memory B Cell Reactivation

Abstract: Memory B cells (MBCs) have enhanced capabilities to differentiate to plasma cells and generate a rapid burst of antibodies upon secondary stimulation. To determine if MBCs harbor an epigenetic landscape that contributes to increased differentiation potential, we derived the chromatin accessibility and transcriptomes of influenza-specific IgM and IgG MBCs compared to naïve cells. MBCs possessed an accessible chromatin architecture surrounding plasma cell specific genes, as well as altered expression of transcri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…B cells from Montanide-adjuvanted mice showed increased expression of the transferrin receptor TFRC-1, which mediates the immune cells uptake of transferrin-bound iron from serum ( 27 ). Iron uptake, in turn, is closely related to the activation of Heme biosynthesis ( 57 ). It has been shown that Heme physically interacts with Bach2, an essential transcription factor that regulates the fate of B lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B cells from Montanide-adjuvanted mice showed increased expression of the transferrin receptor TFRC-1, which mediates the immune cells uptake of transferrin-bound iron from serum ( 27 ). Iron uptake, in turn, is closely related to the activation of Heme biosynthesis ( 57 ). It has been shown that Heme physically interacts with Bach2, an essential transcription factor that regulates the fate of B lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…They found that genes involved in Plasma Cell differentiation showed accessible chromatin in their surroundings. The heme biosynthesis signature is also conserved between rodents and humans, and treatment with Hemin promoted the changes in the metabolism of memory B cells, stimulating oxidative phosphorylation and differentiation to Plasma cells ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although interesting, the progressive upregulation this pathway had been previously appreciated in B cell to ASC differentiation. 120 , 121 …”
Section: Asc Response In Sars‐cov ‐2 Infe...mentioning
confidence: 99%
“…Integrative analysis of transcriptome factors, including mRNAs, miRNAs, lncRNAs, chromatin accessibility, and cis-regulatory elements, revealed a core mRNA-noncoding RNA transcriptional signature of human memory B cells [ 100 ]. Memory B cells have an accessible chromatin architecture around several plasma cell-specific genes, including Xbp1 , Prdm1 , and Irf4 , suggesting the reactivation potential of memory B cells [ 101 ].…”
Section: Epigenetic Modifications Regulate B-cell Differentiationmentioning
confidence: 99%